The influence of entrepreneurial orientation on competitive advantage, as well as its implications for marketing performance in Bag Msmes in Bogor - Muniroh, Leny; Diposumarto, Ngadino Surip; Muharam, Hari (Eximia, 2023)
The role of MSMEs currently has an impact on post-pandemic economic recovery and a number of problems faced in the last 3 years on their business performance, potential factors in their business performance include entrepreneurial orientation, knowledge management, and partnership strategies in increasing innovation and adaptability, besides that Knowledge management also plays an important role in improving MSME performance by facilitating knowledge management which is effective. Partnership strategies, especially with parties that have market access and a wide network, can expand market share and increase product exposure. Therefore, the purpose of this study is to understand the influence of each of these factors on MSME marketing performance and how these factors interact in the context of MSMEs in Bogor Regency, a survey of 176 samples of MSMEs in Bogor Regency uses a quantitative approach to prove the research hypothesis through structural equation modeling. The novelty of this research is an analysis of Internal Resources factors, Digital Marketing, and Partnership Strategies that have an impact on Marketing Performance. This study concludes that if the increase in Internal Resources has an impact on marketing performance behavior and provides competitive advantages, besides that digital marketing can also have an impact on strengthening products to be able to compete and partner relationships will have an impact on products, services, and materials produced, this conclusion confirms the importance of quality internal resource management in an effort to achieve success in the bag business. This research posits both theoretical and practical implications, and limitations of the study